IMPLEMENTASI NILAI-NILAI PENDIDIKAN ISLAM PADA ORGANISASI ROHANI ISLAM DAN KONTRIBUSINYA TERHADAP PESERTA DIDIK DI MADRASAH ALIYAH IMAM ADIL RAJA AMPAT - Labagu, Husnul Khotimah Indah (Pascasarjana IAIN Sorong, 2025)
The aim of this research is First; revealing the implementation of Islamic educational values ​​in the Islamic Spiritual organization at Madrasah Aliyah Imam Adil Raja Ampat. Second; analyzing the contribution of the Rohani Islam organization in implementing educational values. This research uses a descriptive qualitative approach with data collection techniques from observation, interviews and documentation with the spiritist supervisor, spiritist administrator, school principal, deputy head of curriculum and two parents and guardians. The research results show that the implementation of Islamic educational values ​​through Islamic Spiritual Organizations is a forum for students to express or hone their abilities, especially in the religious field. The Islamic Spiritual Organization carries out work programs that can be a means of implementing the values ​​of Islamic education, namely the values ​​of worship, moral values ​​and Aqidah values. The Rohis organization contributes to increase understanding of the value of Islamic education which has an impact on students' better morals and becomes a role model in the Imam Adil Raja Ampat Madrasah Aliyah environment. For this reason, it is hoped that future researchers will be able to explore the development of religious character in schools, in order to obtain more competent strategies.